Pengelolaan Sampah Berbasis Masyarakat Melalui Pendirian Bank Sampah di Desa Kalitengah Cirebon - Anton Sudrajat; Titi Kumala; Perdi Pirmansyah; Nabila Dwi Febriyanti; Adysa Dzikrina Nur Jannah (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2024)
One of the main problems faced by the people of Kalitengah Village, Tengah Tani Sub-district, Cirebon Regency is the lack of awareness about the importance of waste management. Waste that is not managed properly often accumulates in various corners of the village, causing health and environmental problems. To overcome this problem, there is an urgency to increase public awareness and knowledge about good and correct waste management, so programs that support sustainable waste management involving community participation are needed such as the establishment of waste banks to deal with waste problems effectively. The purpose of this empowerment is expected to increase community awareness and active participation in waste management through the establishment of waste banks so that they can solve waste problems independently and sustainably. To carry out this program using the Participatory Action Research (PAR) method which emphasizes the waste problems faced by the community. This empowerment resulted in social change through the formation of a new institution, namely a waste bank based on the joint commitment of the entire community through joint social reflection activities. In addition, local leaders also have an important role in the implementation of the waste bank.